Japan's killer quake - Burke-Ward, Richard; Strange, Robert; Johnson, Corey 1961-.; Pioneer Productions; PBS Distribution (Firm).; Channel Four (Great Britain).; WGBH (Television station : Boston, Mass.). (United States PBS Distribution, 2011)
In its worst crisis since World War II, Japan faces disaster on an epic scale: a rising death toll in the tens of thousands, massive destruction of homes and businesses, shortages of water and power, and the specter of nuclear reactor meltdowns. It combines on-the-spot reporting, personal stories, compelling eyewitness videos, and exclusive helicopter footage for a unique look at the science behind the catastrophe.
Introduction -- The quake -- Tsunami -- Overwhelmed defenses -- Sounding alarms -- After shock.
Edition from disc label.
Originally aired on PBS in 2011.
Camera, Joe Baram ... [et al.] ; editing, Sarah Hewer, Andy Flynn, and Rob Sylvester.
Narrator, Corey Johnson.
DVD, NTSC, region 1; widescreen, stereo.
In English and Japanese with English subtitles; optional English subtitles for the deaf and hard of hearing.
Keywords: Tohoku Earthquake and Tsunami, Japan, 2011.; Fukushima Nuclear Disaster, Japan, 2011.; Earthquakes -- Japan; Tsunamis -- Japan; Nuclear power plants -- Accidents -- Japan; Nuclear power plants -- Earthquake effects -- Japan; Emergency management -- Japan; Documentary television programs; Disaster television programs; Nonfiction television programs; Video recordings for the hearing impaired; Science television programs; Television news programs